2022
DOI: 10.3390/ijms23136918
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy in Psychiatric Disorders: A Narrative Review Exploring Neuroendocrine–Immune Therapeutic Mechanisms and Clinical Implications

Abstract: Electroconvulsive therapy (ECT) is based on conducting an electrical current through the brain to stimulate it and trigger generalized convulsion activity with therapeutic ends. Due to the efficient use of ECT during the last years, interest in the molecular bases involved in its mechanism of action has increased. Therefore, different hypotheses have emerged. In this context, the goal of this review is to describe the neurobiological, endocrine, and immune mechanisms involved in ECT and to detail its clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 188 publications
(232 reference statements)
0
3
0
1
Order By: Relevance
“…Patients with mood disorders, particularly depression, often exhibit disturbed levels of stress hormones. Studies consistently show hyperfunction of the hypothalamic–pituitary–adrenal (HPA) axis in individuals with depression [ 26 ]. This is characterized by elevated cortisol levels and a reduced suppression of cortisol on the Dexamethasone suppression test.…”
Section: Endocrine System Regulationmentioning
confidence: 99%
“…Patients with mood disorders, particularly depression, often exhibit disturbed levels of stress hormones. Studies consistently show hyperfunction of the hypothalamic–pituitary–adrenal (HPA) axis in individuals with depression [ 26 ]. This is characterized by elevated cortisol levels and a reduced suppression of cortisol on the Dexamethasone suppression test.…”
Section: Endocrine System Regulationmentioning
confidence: 99%
“…Auch sind Auswirkungen der EKT auf die endogenen Neurotransmittersysteme beschrieben [5], wie veränderte Bindungskapazitäten von Dopamintransportern bei depressiven Patienten. Zudem gibt es vermehrt Studien, die sich mit einer neuroinflammatorischen Beteiligung bei psychischen Erkrankungen auseinandersetzen, und auch hier könnte die EKT einen therapeutischen Effekt entfalten [6].…”
Section: Wirkungsweise Ther Apieprinzipunclassified
“…However, the molecular mechanism for ECT remains unclear, although some key findings have been reported thus far (Fochtmann, 1998; Bolwig, 2011; Kranaster et al ., 2019; Rojas et al ., 2022). The available clinical studies have shown that the rapid and effective therapeutic effect of electroconvulsive seizures may be related to synaptic plasticity (Chen et al , 2018), inflammatory/immune response (Bioque et al ., 2019) and the genes involved in the T-cell factor family (Kaneko et al ., 2015; Nishiguchi et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%